Ghats on northern end of Banganga Tank - Banganga by Ghosh, Ayan (2023)
The water level in the Banganga Tank is controlled by underground valves and overflow outlets empty into the nearby Arabian Sea. During the monsoon months, the tank can overflow, unless regulated by the outlet valves. When the water level is low, it reveals the natural spring from which water enters the tank, which otherwise remains submerged.